Toda-Yamamoto Causality Test between Inflation and Nominal Interest Rates: Evidence from Three Countries of Europe - Dritsaki, Chaido (International Journal of Economics and Financial Issues, 2017)
This paper investigates the relationship between inflation and nominal interest rates for three European countries, Germany (member of EMU), Great Britain (member country of EU but not EMU) and Switzerland (a non-EU country) from January 1995 until May 2015. For testing the long run equilibrium relationship we use the ARDL cointegration technique (Autoregressive Distributed Lag) developed by Pesaran et al. (2001) as well as Granger no-causality approach developed by Toda and Yamamoto (1995) in a two-variable vector autoregression (VAR) model. The results of ARDL approach (bound test) shown that there is a cointegrated vector for the three examined countries thus Fisher assumption is valid. Finally, the results of Toda and Yamamoto approach show that the nominal interest rate has a positive relationship and affects inflation on a large scale in the three countries that we study, while inflation influences interest rate only in Germany. Keywords: Fisher Effect, ARDL Cointegration Test, Error Correction Model, Toda-Yamamoto Causality Test JEL Classifications: C32, E23, ÎŸ11